THE MASCULINE NOUNS IN MACEDONIAN AND SERBIAN LANGUAGE (PALIMPSEST / ПАЛИМПСЕСТ, 2021)
In the grammars for the Macedonian and Serbian language ​​it’s stated that the morphemes -ov-/-ev- are carriers of the information about the gender and the number of some nouns. Having in mind the different representation of these morphemes in the Macedonian and Serbian language, we will try to review the plural forms of masculine nouns, especially those that receive -ovi/-evi in the plural. In the context of what has been said, we will try to consider its origin, the use in older stages of languages, as well as the changes it undergoes based on some dialectal features of the Macedonian speaking area.             Keywords: masculine nouns, plural, morpheme, Macedonian language, Serbian language.